KANDUNGAN PROKSIMAT DAN KOMPOSISI ASAM OKSALAT PADA KULIT UMBI TALAS BENENG YANG TUMBUH LIAR PADA KONDISI KETINGGIAN TEMPAT YANG BERBEDA - Eltis Panca Ningsih; Nuniek Hermita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Talas Banten was better known with the name beneng which is called for besar and koneng, and had meaning large and yellow. Taro beneng was derived from Pandeglang Regency of Banten Province. This research was aimed to know the nutrient content, composition, oxalic acid and mineral content in the talas beneng skin are growing wild by the community at different places. The research was carried out from May until October 2016. This research was conducted in the form of field research around the area of Mountain Coral, Pandeglang Regency, Banten Province. Analysis of the talas beneng skin was done in Balai Besar Industri Agro, Bogor. The results showed that the content of proksimat talas beneng skin was growing wild include water, ash, protein, fat and carbohydrates. Moisture content at an altitude of 500 m above sea level was higher (87.1%) compared to a height of 650 m above sea level (86.2%) and an altitude of 800 m above sea level (86.8%). Ash at a height of 650 m above sea level is higher (3.48%) compared to an altitude of 500 m above sea level (2.52%) and an altitude of 800 m above sea level (2,26%). Protein content and fat at an altitude of 500 m above sea level is higher (1.54% and 0.34%) compared to a height of 650 m above sea level (1.08% and 0.19%) and height 800 mdpl (1.08% and 0.11%). Content of carbohydrate at a height of 800 m above sea level was higher (9.75%) compared to an altitude of 500 m above sea level (8.50%) and an altitude of 650 m above sea level (9.05%). Content of oxalic acid at a height of 650 m above sea level was higher (0.19%) than an altitude of 500 m above sea level (0.11%) and height 800 m above sea level (0.12%).